Perceptions and practices of government hospital pharmacists (ministry of health) towards antimicrobial stewardship program in state of Selangor / Muhammad Syafiq Saleh - Saleh, Muhammad Syafiq (2017)
Antimicrobial resistant has become a major healthcare issues nowadays. Antimicrobial stewardship (AMS) were introduced to promote proper use of antimicrobial agents and to overcome antimicrobial resistance problems. The main objective of this study was to assess pharmacists’ perceptions and practices towards AMS program in hospital pharmacy settings. A cross-sectional study was conducted among pharmacist in Selangor from December 2016 to January 2017. Questionnaires were distributed mostly online. Total pharmacists included were 432 and all were universally sampled for the purpose of this study. Total of 199 participants responded to the survey giving a response rate of 46%. The majority of the respondents strongly agreed (n = 102, 52.4%) or agreed (n = 88, 43.5%) that AMS programs improve patient care in hospitals (Median = 5; IQR = 3). Interestingly, about less than half of the respondents indicated that local antibiotic guidelines were always (n = 49, 24.9%) or often (n = 46, 23.4%) established in their hospitals (Median = 3, IQR = 4). Gender of the participants affected their median score with respect to their practices in AMS (median score: male = 3 versus female = 4) with the significance p value of 0.007. Similarly, years of practicing has significantly affected the median perception score towards AMS (p = 0.043). Qualification of the respondents has a significant impact on their median scores pertaining to both perception (p = 0.03) and practices (p = 0.019) towards AMS. In overall, the perception and practices towards AMS were positive. Results obtained cannot be generalized as it only reflects pharmacists in the state of Selangor.